2013
DOI: 10.1111/j.1755-3768.2013.s002.x
|View full text |Cite
|
Sign up to set email alerts
|

Augmented dried versus cryopreserved amniotic membrane as an ocular surface dressing

Abstract: Purpose: Dried amniotic membrane (AM) can be a useful therapeutic adjunct in ophthalmic surgery and possesses logistical advantages over cryopreserved AM. Differences in preservation techniques can significantly influence the biochemical composition and physical properties of AM, potentially affecting clinical efficacy. This study was established to investigate the biochemical and structural effects of drying AM in the absence and presence of saccharide lyoprotectants and its biocompatibility compared to cryop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Okabe et al found that the structures of collagen fibers in the connective tissues were not destroyed by the hyperdry device and were more stable than cryopreserved AM [7]. Allen et al also showed that the biochemical composition of the dried AM, including the number of factors such as epidermal growth factor and TGF-β1, were similar to fresh AM [22]. Moreover, rabbit models have also shown that HD-AM can be at least as efficacious as cryopreserved AM when used as a substrate for ocular surface reconstruction [23].…”
Section: Discussionmentioning
confidence: 88%
“…Okabe et al found that the structures of collagen fibers in the connective tissues were not destroyed by the hyperdry device and were more stable than cryopreserved AM [7]. Allen et al also showed that the biochemical composition of the dried AM, including the number of factors such as epidermal growth factor and TGF-β1, were similar to fresh AM [22]. Moreover, rabbit models have also shown that HD-AM can be at least as efficacious as cryopreserved AM when used as a substrate for ocular surface reconstruction [23].…”
Section: Discussionmentioning
confidence: 88%
“…Described bio-objects can be used to produce stem cells [14,20], in an experiment, testing of pharmaceuticals [10], auto-banking [17], for laboratory studies [7,9]. Fetal membranes are used as scaffolds for constructions in tissue engineering [15,16], allografts in reconstructive surgery [11,18] and ophthalmology [13,6]. Several studies have considered the expediency of isolating cells not from the native, but from the frozen placental material [19], which greatly simplifies the technology of low-temperature banking, eliminating the need to isolate cells in a short time after the birth of the placenta.…”
Section: Institute For Problems Of Cryobiology and Cryomedicine Of Thmentioning
confidence: 99%
“…7,8,9 The h AM has the additional advantage of abundant availability, and has been clinically used in other applications with success for over a century. 10-13 While a cell-mediated fusion of the layers has proven successful in preliminary studies, this study investigated the use of freeze-drying in conjunction with a fibrin sealant to bind adjacent layers. 6,14 Without the need for pre-population with autologous cells, the conduits would be readily available, easily transportable, and storable extended time periods.…”
Section: Introductionmentioning
confidence: 99%